Depressive Behavior of Rats Consuming Cocoa Powder and Cocoa Extract - Ariza Budi Tunjung Sari; Misnawi Misnawi; Pratiwi Pudjiastuti; Afaf Baktir (Indonesian Coffee and Cocoa Research Institute, 2018)
Chocolate is associated with calm and happy feelings. However little is found to demonstrate if this effect is induced by active ingredient in cocoa ratherthan the sweetness of chocolate. In this study we tested the effect of cocoa on the depressive behavior of female rats suffering from estrogen deficiency. Twentyfemale rats aged seven weeks old were ovariectomized to remove the estrogen source. The rats were distributed into four groups and undergoing three dayoral administration of 1g/kg body weight (bw) cocoa powder, 1g/kg bw cocoa extract, 1 mg/kg bw estradiol valerate and 1 mL/kg bw vehicle (olive oil). Anothergroup of rats having intact ovaries received 1 mL/kg bw drinking water. The rats were undergoing forced swimming test (FST) one day before treatment and after treatment and the immobility time was recorded. No significant difference was found on the after-treatment immobility time across groups. However, all the rats in the vehicle group developed longer immobility time after-treatment compared with the result from before-treatment test, suggesting that depression had occurred in ovariectomized rats receiving no active substances. In the other hand, very few rats had greater after-treatment immobility time in the cocoa powder and estradiol valerate groups. In the cocoa extract group, all the rats had shorter immobility time after treatment when it is compared with before treatment time. We conclude that compounds in cocoa have certain extent of estrogenic activity that affects emotional state.